Legal Implications of Authority Regulation for Prevention and Eradication of Institution of Forest Destruction in Law Number 18 of 2013 Concerning Prevention and Eradication of Forest Destruction - Eko Tjahjono,; Sudarsono,; Abdul Rachmad Budiono ,; Abdul Madjid , (Technium Social Sciences Journal, 2021)
Forests in Indonesia need to be continuously preserved from the company's activities in using forest areas illegally and organized individuals who carry out illegal logging activities that continue to occur every year. Efforts to preserve forest have been embodied in Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction, which includes the Authority for the Prevention and Eradication of Forest Destruction to carry out investigations up to investigations into criminal acts of forest destruction as stipulated in Article 56 paragraph 1 and in activities to eradicate forest destruction, the institution may form a task force as an implementing element. The task force carries out the eradication of forest destruction that is strategic from the investigation to the prosecution throughout the territory of the unitary state of the Republic of Indonesia, including the territory of the head of the institution and/or deputies under the provisions of Article 55 paragraph 5. The power to prosecute the task force has legal implications with other laws and institutions with prosecution authority.